Understanding Health Empowerment From the Perspective of Information Processing: Questionnaire Study - Fei Jiang; Yongmei Liu; Junhua Hu; Xiaohong Chen (JMIR Publications, 2022)
BackgroundMassive, easily accessible online health information empowers users to cope with health problems better. Most patients search for relevant online health information before seeing a doctor to alleviate information asymmetry. However, the mechanism of how online health information affects health empowerment is still unclear. ObjectiveTo study how online health information processing affects health empowerment. MethodsWe conducted a cross-sectional questionnaire study that included 343 samples from participants who had searched online health information before the consultation. Respondents' perceptions of online information cues, benefits, health literacy, and health empowerment were assessed. ResultsPerceived argument quality and perceived source credibility have significant and positive effects on perceived information benefits, but only perceived argument quality has a significant effect on perceived decision-making benefits. Two types of perceived benefits, in turn, affect health empowerment. The effects of perceived argument quality on perceived informational benefits and perceived decision-making benefits on health empowerment are significantly stronger for the high health literacy group than the low health literacy group (t269=7.156, P<.001; t269=23.240, P<.001). While, the effects of perceived source credibility on perceived informational benefits and perceived informational benefits on health empowerment are significantly weaker for the high health literacy group than the low health literacy group (t269=-10.497, P<.001; t269=-6.344, P<.001). The effect of perceived argument quality on perceived informational benefits shows no significant difference between high and low health literacy groups. Conclusions In the context of online health information, perceived information benefits and perceived decision-making benefits are the antecedents of health empowerment, which in turn will be affected by perceived argument quality and perceived source credibility. Health literacy plays a moderating role in the relationship of some variables. To maximize health empowerment, online health information providers should strengthen information quality and provide differentiated information services based on users' health literacy.